Analysis of Electrical Voltage Instability Causes in Auxiliary Engine No. 2 Aboard MV. HANGLIMA - Bima Nurrahma; Antonius Edy Kristiyono; Agus Prawoto; Shofa Dai Robbi; Sri Mulyanto (Journal of Engineering Science and Technology Management, 2026)
This study investigates the factors contributing to electrical voltage instability in Auxiliary Engine No. 2 aboard MV. Hanglima. The research was motivated by operational disruptions where the voltage output dropped significantly from the standard 440V to 290V, leading to blackouts when the generator operated independently. Employing a qualitative research method utilizing the Fishbone (Ishikawa) diagram for root cause analysis, data was collected through onboard observation, documentation, and interviews with the engineering crew. The analysis revealed that the instability was primarily caused by mechanical failure in the alternator bearings, which had approached their operational limit, leading to an unbalanced rotor rotation. This mechanical imbalance caused friction between the rotor and stator, resulting in insulation leakage (short circuits) within the windings. Corrective measures implemented included a comprehensive overhaul, re-insulating the rotor and stator windings using insulating varnish, and replacing the worn bearings. These actions successfully restored the voltage output to a stable 445V, ensuring the safety and efficiency of the vessel's electrical system.